Video Editing Training to Improve the Quality of Teaching and Learning at SMK Palapa Bandarlampung - Adhie Thyo Priandika; Permata Permata; Rakhmat Dedi Gunawan; Temi Ardiansah; Mico Fahrizal; Anggun Maylani; Annisa Anggraini (Universitas Teknokrat Indonesia, 2022)
The teaching and learning process is very important in the teaching and learning process. Learning objectives or instructional objectives are learning outcome behaviors that are expected to occur, be owned, or be mastered by students after participating in certain learning activities. Previously, teachers found it difficult to develop learning video editing. This is due to the limitations of human resources who understand the use of information technology devices, especially video editing. From the results of the questionnaire distributed, 92.5% of respondents said they were satisfied with the video editing training that had been made. Thus, the learning video editing training that has been made by the teachers can be declared feasible and can be used as learning material.